Quantitative distribution patterns of selected Lower to Middle Miocene calcareous nannofossils from the Ontong Java Plateau. - FORNACIARI, ELIANA; RIO, DOMENICO; BACKMAN I. (Ocean Drilling Program:1000 Discovery Drive:College Station, TX 77845:(409)845-2016, EMAIL: distribution@odp.tamu.edu, jennifer--rumford@odp.tamu.edu, INTERNET: http://www-odp.tamu.edu/publications/, Fax: (409)845-4857, 1993)
Uppermost Oligocene through middle Miocene calcareous nannofossil events that were considered potentially useful from a biostratigraphic point of view have been investigated from Ocean Drilling Program Sites 806 and 807 in the western equatorial Pacific Ocean. Comparisons have been made to the corresponding events from other equatorial regions and the mid-latitude North Atlantic. In terms of biostratigraphic reliability, defined by the ability of the pertinent species to provide distinctive marker events and synchroneity over geographic distance, the investigated events can be classified into four general categories: good markers, poor markers, ecologically controlled markers with regional value and low abundance markers.